‘The Ill-name of the Old Country’: London’s Assisted Emigrants, British Unemployment Policy, and Canadian Immigration Restriction, 1905-1910 - Scott, Elizabeth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
Between 1906 and 1910, Canada passed two increasingly restrictive Immigration Acts to, among other reasons, reduce charitable assisted emigration from London. These acts were passed in response to Britain’s Unemployed Workmen Act in 1905, which contained an emigration clause designed to move London’s unemployed to Canada. Canada deemed these emigrants to be unsuitable largely because they hailed from the impoverished East End of London. Emigration charities felt an imperial betrayal in the wake of the restrictions. Although an exception allowed for a limited degree of charitable emigration to continue, assisted English emigrants were now unreservedly lumped together with other undesirables in the British World. Despite Canadian displeasure, charities continued to send London’s unemployed to Canada until World War I. A more direct relationship between British unemployment policy and Canadian immigration policy is emphasized, opening a space wherein to examine transnational and imperial legal tensions in the early twentieth century British World. This space reveals a nexus of poverty, migration, and restriction that pitted Britain’s needs against Canada’s; it also complicates the concept of loyal nations belonging to a cooperative British World, becoming particularly relevant to the evolution of restrictive Canadian attitudes towards British immigrants after 1905.